Development of Interactive Digital Modules Based on Augmented Reality - Salim Salim; Rahmad Prajono; La Misu; Hendra Nelva Saputra (AL-ISHLAH: Jurnal Pendidikan, 2022)
Interactive digital modules have now become a new commodity in the world of learning that must be a major concern in order to facilitate an efficient and flexible learning process. The purpose of this development is to create augmented reality to be used as a learning resource by all academics. This study uses the Lee Owens development model which consists of 4 stages, namely assessment/analysis, design, development and implementation, and evaluation. This development activity involved a learning media expert, a material expert, and 8 small group pilots to assess the feasibility of the digital module being developed. Based on the presentation of the validator's assessment of the augmented reality, it can be concluded that augmented reality is very valid criteria which means it is very good for use in learning with a percentage of 90.25% of media experts, 88.75% from material experts, and 86.5% from small group trials. Researchers recommend using this material as a learning resource for Information Technology courses that can be accessed on the Halu Oleo University website. Researchers also suggest making augmented reality as part of the learning materials developed.